The art of war in the sixteenth century - Oman, Charles, 1860-1946 (London : Greenhill Books, 1987)
Military geography, strategie and tactics - The French, Spanish, Swiss, Germans and Italian army The great battles of the Italian Wars (1495-1559) - The military history of England under the Tudors - The wars of religion in France 1562)1598) - The revolt in the Netherlands (1568-1609) -The Turkisch attack on Christendom (1520-1606)